Nitric oxide and arginase levels in peri-implant tissues after delayed loading. (January 2018) - Gokmenoglu, Ceren; Ozmeric, Nurdan; Sungur, Caglar; Sahin Bildik, Raziye; Erguder, Imge; Elgun, Serenay
Highlights: We evaluated the levels of nitric oxide and arginase levels in PISF and saliva after implant loading. Salivary nitric oxide and arginase levels did not show any change after loading. Both nitric oxide and arginase levels around implants showed an increased from baseline to 3 and 6 months. PISF might provide more information than saliva. Abstract: Objective: Nitric oxide (NO) is synthesized from the conversion of L-arginine to L-citrulline by NO synthase (NOS). Arginase can compete with NOS for the common substrate L-arginine, and thus inhibit NO production. NO levels and arginase ezyme might affect the bone remodeling cycle around implants. The aim of this studywas to investigate NO and arginase levels in gingival crevicular fluid (GCF), peri-implant sulcular fluid (PISF), and saliva. Materials and methods: Twenty patients with one or more implants (Straumann ® ; Institute Straumann AG, Basel, Switzerland) restored with fixed crown prostheses were included in the study. Plaque index (PI), gingival index (GI), probing depth (PD), and bleeding on probing (BOP) were recorded from six sites of each tooth and implant at baseline and at months 1, 3, and 6 after loading. The saliva, GCF, and PISF were collected at baseline and at months 1, 3, and 6 after loading. NO level and arginase enzyme were evaluated in GCF, PISF, and saliva. Results: Arginase and NO levels in saliva did not change significantly from baseline to months 1, 3, and 6. However, both PISF NO and arginase levels showed an increased pattern from baseline to month 6. NO levels were significantly higher at months 3 and 6, compared to baseline, while PISF arginase levels increased significantly from baseline to months 3 and 6. Conclusion: NO and arginase enzyme measurements in saliva, GCF, and PISF may be beneficial in the determination of current peri-implant tissues. In particular, PISF might provide more information than saliva.